Reversed Phase HPLC Studies on the Change of the Content of Organic Acids in Tobacco During Aging - Guo, Jun-Cheng; Guo, Zhen; Cheng, Xiao-Lei; Wang, Neng-Ru; Ming, Ning-Ning (Asian Journal of Chemistry, 2010)
Tobacco leaf samples from different leaf positions, different aging time were extracted for the determination of organic acids. Organic acids in tobacco have been determined by RP-HPLC method combined with UV detection. The gradient mobile phase employed was 20 mM phosphate buffer (pH 2.6) and acetonitrile at a flow-rate of 1.0 mL/min. Recoveries for organic acids were in the range of 84.2 to 106.3 %. The relative standard deviation of the repeating of the migration time and peak area of five replicate analyses of 11 organic acids ranged from 0.42 to 1.78 % and from 0.47 to 2.5 %, respectively. The results show that organic acids concentrations varied with aging time and different leaf position.